Optimization of Insulin Yield from Extract of Stevia Leave (Rebaudiana Bertoni) - Abubakar, Muhammad Abbagoni; Abubakar, Abdulhalim Musa; Abubakar, Musa Askira; Dahiru, Dahiru Muhammad (International Journal of Multidisciplinary Approach Research and Science, 2023)
Stevia (Rebaudiana bertoni) leave, is an ancient perennial shrub mostly found in South America such as Paraguay and Brazil, it contains a low-calorie sweetener, which is about 300 times sweeter than sucrose. Insulin is a polypeptide hormone, which has an anabolic property, insulin has a vital role in regulation of carbohydrate metabolism, it also enhances the metabolism of fat and proteins and regulation of certain gene expression. Design expert software 10.0 was used to design the experimental data for the optimization of insulin yield in stevia (Rebaudiana bertoni) leave. Custom design with 3 factor and one response was applied, the independent variables were amount of stevia powder (g), volume of n-hexane (ml) and volume of ethyl acetate (ml) and the response is percentage of insulin yield (%). In this research work, insulin was successfully extracted from stevia (Rebaudiana bertoni) leave and the optimum yield was determined. The optimum extraction conditions for optimum yield of insulin were found to be: 5.668 g of stevia powder, 49.107 ml of n-hexane and 32.386 ml of ethyl acetate.